Respectful community engagement in health research with diverse im/migrant communities - M Ruth Lavergne; Shira Goldenberg; Mei-ling Wiedmeyer; Stefanie Machado; Samira Karsiem (BMJ Open)
Introduction Global migration and immigration are increasing, and migrants and immigrants (im/migrants) have specific health needs and healthcare experiences. Yet, im/migrant involvement in immigration and health research in Canada is inconsistent. Heretofore, involvement has primarily been in research planning, data collection and analysis, with little community involvement during knowledge exchange or through training and colearning opportunities. Community engagement has been especially uncommon in mixed-method and quantitative research in Canada.Objective This article describes lessons learnt from the Evaluating Inequities in Refugee & Immigrants’ Health Access (IRIS) project from 2018 to 2023, an ongoing mixed-method, community-based research project in British Columbia, Canada. Specifically, we share our core community engagement project structures, Commitments to Community and our Community Engagement Backbone, both collaboratively developed with im/migrant community memebers.Participants People with varied experiences of im/migration and connections to multiple, specific im/migrant communities participate in the project as participants, community researchers, community advisory board members, faculty members and students. Core research activities are supported in English, Farsi, Spanish and Tigrinya. We engage community members throughout the research process, from identifying research topics to knowledge exchange.Conclusion We found that these structures offer an accessible visual representation of the project’s commitments to community engagement, and the ways these commitments are demonstrated through values and action. Our training opportunities, colearning activities and knowledge exchange efforts also confirmed the accuracy of interpretation, prompted additional analysis to clarify or add depth to findings, and helped us identify additional research topics. We hope these learnings can be used to expand engagement with diverse im/migrant communities in health and immigration research.